Can a simple plan change a complex behavior? Implementation intentions in the context of water drinking. (1st April 2023) - Rodger, Amy; Vezevicius, Ariel; Papies, Esther K.
Abstract: Underhydration has significant adverse physical and mental health effects, yet many people drink too little water. Implementation intentions have been found to effectively promote many health behaviors, but little is known about the processes underlying their effects in naturalistic settings, and whether they could improve water drinking. This mixed-methods study assessed the impact and potential underlying processes of using implementation intentions to increase self-reported water intake over a five-day follow-up. Ninety-five participants ( M age = 39, SD  = 12) received an educational quiz to increase their water drinking motivation before being randomly assigned to the control or intervention group. Participants also completed a qualitative survey that assessed the processes underlying their attempts to increase water intake. Quantitative results suggested that most participants increased their average daily water intake regardless of group. Qualitative results indicated that implementation intention participants struggled with remembering and the perceived effort of preparation and drinking behaviors, which reduced the effect of planning on behavior. This study provides essential theoretical and methodological considerations for researchers studying implementation intentions, as the effects and mechanisms of implementation intentions in real-life situations may be more complex than previously assumed. For example, the results suggest that implementation intentions did not automatize remembering and performing the behavior in ways the current literature theorizes. Other kinds of interventions may be needed to improve the complex daily-life behaviour of water drinking.